Proceedings of the 11th International Conference on Automotive User Interfaces and Interactive Vehicular Applications 2019
DOI: 10.1145/3342197.3344546
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Messages Conveyed by Automated Vehicles

Abstract: This is a repository copy of Understanding the Messages Conveyed by Automated Vehicles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 19 publications
3
24
0
Order By: Relevance
“…Of course, visibility of eHMI is perhaps not the only factor to explain this phenomenon, since the SPLB was perceived around 27.5 m away, yet did not prompt as many crossings. A previous study (Lee et al, 2019c), showed FH to be ranked significantly higher than SPLB for conveying the message 'I am giving way', and, at least in the west (Honest, 2004), this cue is associated with such a communication message. Although the UK Highway Code,…”
Section: Percentage Of Crossingsmentioning
confidence: 88%
See 4 more Smart Citations
“…Of course, visibility of eHMI is perhaps not the only factor to explain this phenomenon, since the SPLB was perceived around 27.5 m away, yet did not prompt as many crossings. A previous study (Lee et al, 2019c), showed FH to be ranked significantly higher than SPLB for conveying the message 'I am giving way', and, at least in the west (Honest, 2004), this cue is associated with such a communication message. Although the UK Highway Code,…”
Section: Percentage Of Crossingsmentioning
confidence: 88%
“…Table 2 shows the range of behaviours and eHMI combinations experienced by the two groups. (Lee et al, 2019c). Therefore, these two messages were chosen for further investigation in the current study, to understand the effect of context and actual crossing behaviour, on the perception and comprehension of each signal.…”
Section: Designmentioning
confidence: 99%
See 3 more Smart Citations